New Geophysical Data About the Pacific Margin (West Antarctica) Magnetic Anomaly Sources and Origin - Soloviev, V. D.; Bakhmutov, V. G.; Korchagin, I. N.; Yegorova, T. P. (Ukrainian Antarctic Journal, 2018)
During the seasonal work in the Ukrainian Antarctic expeditions (1997—2012), a significant amount of geological and geophysical studies were carried out. The main objective of the study is to obtain new data on the distribution of deep heterogeneities in the structures of the region. It’s allowed to construct the geophysical models and to discuss the existing ideas about the stages of formation and evolution tectonic structures of the West Antarctica near the Antarctic Peninsula (AP). New geophysical models of the Earth’s crust were used to study the possible nature of the Pacific Coast magnetic anomaly (PMA) near the AP. The results of magnetic, seismic and geoelectric surveys in the region of the Antarctic Peninsula showed that active tectonic processes in the Meso — Cenozoic led to the of PMA magnetic sources forming along the edge of the AP. The spatial heterogeneity of the various segments of PMA can also be associated with a variety of depth, thickness and magnetic susceptibility of individual units that form the source of regional anomaly. The magnetic PMA sources in the Earth’s crust can be limited in depth (up to 8—10 km) and consist of a series of bodies with different age, composition and magnetization. The shape of the PMA anomalies is significantly affected by numerous local intrusions located in the upper part of the earth’s crust. In certain segments of the PMA, they form an additional horizon of magnetized bodies associated with the processes of young volcanism in the structures of the continental margin. Conclusions. The materials of geophysical surveys and complex geological and geophysical models of the earth’s crust and upper mantle were analyzed, which made it possible to identify structural features, evolution, and geodynamic processes of the development of regional structures, as well as to obtain new data on the possible nature of PMA. The total anomaly name (PMA) can formally integrate anomalies of different ages and origins. Numerous local intrusions of young (Cenozoic) age form an additional horizon of magnetized bodies associated with volcanic processes at the top of the crust. Some segments of the PMA may be associated with the processes of tectonic changes near the Antarctic — Scotia paleo-plate boundary, as well as teсtonic and magmatic activity in the areas of paleorift structures detection. New geophysical results for different PMA — segments from the Palmer Land to Powell Basin were used to summarize current ideas about the sources and origins of this positive magnetic anomaly.